High-temperature effects on white cement-based slurry infiltrated fiber concrete with metakaolin and fly ash additive - Aygörmez, Yurdakul; Al-mashhadani, Mukhallad M.; Canpolat, Orhan (Revista de la Construcción. Journal of Construction, 2020)
In this present study, the high flexural parameter properties of SIFCON were examined, while the use of metakaolin and fly ash with PC 52.5 CEM I R was examined. 5 series were prepared and replaced with metakaolin and fly ash 25% and 50%. 5% of steel fiber was used in all series and the results of 7 and 28 days flexural and compressive strengths, and ultrasonic pulse velocity were examined. Given the 28-day test period, strength increase was observed in metakaolin-added samples, while lower results were obtained in fly ash-added samples since fly ash has not yet been completely hydrated. When the 28-day compressive and flexural strength results were examined, the highest results were achieved with 57.39 MPa and 44.53 MPa in series 4 with the pozzolans’ hydration. SIFCON is a material that can be used in different areas, such as military buildings. In these buildings, it is necessary to examine the circumstances after the impact of the explosion and fire. For this purpose, high-temperature testing is required. After the 200, 400 and 600 oC of temperature test, the results of flexural and compressive strengths, ultrasonic pulse velocity and weight loss were examined. The increase in strength after the 300 oC temperature can be caused by drying shrinkage of the matrix, whose C-S-H structure is not yet intact, and compression of the fiber wall. The conversion from Ca(OH)2 to Cao begins at about 400 oC, and the C-S-H structure is quickly destroyed as it approaches 600 oC. Cracks in the distribution, similar to the branching of cracks in non-fiber samples, were much narrower on the surface of SIFCON samples